Mineral Utilization in Rams Fed Ration Supplemented with Different Levels of Chromium, Calcium, and Cation-Anion Balances - D Sudrajat; T Toharmat; A Boediono; I G Permana; R I Arifiantini; F Amir (Faculty of Animal Science, Bogor Agricultural University, 2011)
Chromium (Cr) is an essential mineral for ruminants. Its metabolism and interactions with other minerals has not been widely known. This experiment was designed to evaluate the utilization of minerals and growth of Garut ram fed ration supplemented with Cr and different Dietary Cation Anion Balance (DCAB) and Ca level. Dietary treatments, namely: R0 (Ration with DCAB+14); R1 (Ration with DCAB+14 + Cr 3ppm,); R2 (Ration with DCAB 0 + Ca); R3 (Ration with DCAB 0 + Cr 3 ppm + Ca), were allocated in twenty four of 1.5-2 years old Garut rams in a randomized block design. The results showed that Cr supplementation in rations containing different levels of Ca did not affect feed intake, body weight gain, and dry matter digestibility, but reduced the absorption of Cr and Ca of the low Ca diet. Supplementation of Cr had no effect on Cr, Ca, Zn, and Mg status in blood and semen of the rams. Level of Cr intake had negative correlation with Ca absorption and positive correlation with blood Cr levels. There is a positive relationship between level of Ca intake with Ca and Mg absorption and blood Ca and Zn levels. Intake of Cr and Ca was not related to the semen Cr and Ca levels.